Distribution Design of Bottled Mineral Water ‘Airku’ with Distribution Requirement Planning Method (DRP) : (Case Study PDAM Tirta Binangun Kulon Progo) - Trio Yonathan Tejakusuma; Atika Khoirun Nisa; Vindy Fitriana Martanti (Journal of Industrial Engineering and Halal Industries, 2022)
PDAM Tirta Binangun Kulon Progo is a regional manufacturing company that produce gallon, cup and bottle packing mineral drinking water branded AirKu. The company use multi-echelon distribution network for the distribution system. Common problem that encountered by the company is insufficient or exceeded amount of product as a result of fluctuating demand from Agentt, furthermore the Agentt often find it hard to estimate the exact time for product to arrived. PDAM Tirta Binangun need a reliable model of planning and inventory system, and the method that can be used on their multi-echelon network distribution system is Distribution Requirement Planning (DRP). Distribution Requirement Planning is used to determine distribution activity that depend upon safety stock, lead time, inventory cost, order cost, and demand’s forecast. The model is designed based on lot size that have the optimal cost to determine the gross requirement total, project on hand, net requirement, planned order receipt, planed order release and distribution cost. According to company’s document, interview, and calculation the proper lot is Wagner Within Algorithm, distribution cost paid by Agentt Aneka Usaha is Rp 1.768.076 for AirKu cup, Rp 781.388 for bottle AirKu, and Rp 174.275 for AirKu gallon. Distribution cost paid by Agentt Post Office is Rp 881.630 for AirKu cup, Rp 300.613 for bottle AirKu, and Rp 228.375 for AirKu gallon. Distribution cost paid by Agentt Umar is Rp 1.766. for AirKu cup, Rp 579.325 for bottle AirKu, and Rp 454.256 for AirKu gallon. Distribution cost paid by Agentt Joko Sendang is Rp 1.903.623 for AirKu cup, Rp 656.506 for bottle AirKu, and Rp 189.450 for AirKu gallon.